Study of maternal near miss and mortality in obstetrics in a tertiary care hospital - Ninama, Pallavi G.; Karnavat, Ronak D.; Siddhpura, Shivani T.; Karia, Jil P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Maternal health is an important aspect for the development of any country in terms of increasing equity and reducing poverty. In 2009, WHO came up with clinical, laboratory and management criteria for identification of the maternal near miss cases. Aim of the current study was to determine the level of near-miss maternal morbidity and mortality due to severe obstetrical complications or maternal disease in a tertiary care hospital. Objectives of the study were to compare the relation of near miss events with that of maternal mortality and to see the trend of near miss events. Methods: Cases were defined based on WHO criteria 2009. Study was conducted at GMERS Medical College and Hospital, Sola, Ahmedabad from 2020 to 2021. The study population were near miss cases and maternal deaths. Results: During the period of audit there were a total of 6776 deliveries, 6434 live birth, 145 near miss and 36 maternal deaths. Conclusions: Haemorrhage and hypertension are the leading cause of maternal near miss and maternal mortality in our hospital. As near miss indices represent quality of health care it should be represented in the national indices.